Profane illumination through essayistic writing and thinking - Keunen, Bart (Primerjalna književnost, 2010)
This article points at the contrast between the empty concept of experience that was introduced by Enlightenment thinkers and the "essayistic" way of redeeming experience that can be traced back from Erasmus to Perec. The argument links the theory of everydayness of Lefebvre with Benjamin's concept of "illumination" and with Bakhtin's ideal of a "prosaics".
Keywords: Benjamin, Walter, 1892-1940; Bahtin, Mihail, 1895-1975; literarna teorija; literary theory; esej; esejističnost; iluminacija; prozaika